New developments in the area of topological insulators - Felser, Claudia; Yan, Binghai; Muechler, Lukas; Chadov, Stanislav; Kuebler, Juergen; Zhang, Shoucheng (AIP Conference Proceedings, 2015)
Topological insulators are a hot topic in condensed matter physics. A new topological insulator has been identified in cerium-filled skutterudite (FS) compounds.
CRIS-Team Scopus Importer:2023-03-20